Zagadka smierci Stalina : spisek Berii - Avtorkhanov, Abdurakhman, 1908- (London : Polonia, 1983)
Polish translation of "Zagadka smerti Stalina". A biography of Stalin.
Keywords: Stalin, Joseph, -- 1879-1953.; Beriia, L. P. -- 1899-1953.; Statesmen -- Soviet Union -- Biography; Soviet Union -- Politics and government -- 1936-1953.